Equivalent Circuit Models for Determination of the Relation between the Sensing Behavior and Properties of Undoped/Cr Doped TiO2 NTs - Yakup Gönüllü (Chemosensors, 2014)
High-temperature gas sensing requires the increase of sensitivity and reduction of cross-sensitivity. The use of TiO2-Nanotubular layers as gas sensors has shown that the selectivity and sensitivity can be influenced by doping with trivalent elements and by optimization of morphological aspects such as pore diameter and nanotube length. In this work, focus has been given on the understanding of the effect of doping and properties of nano-tubular TiO2-layers on sensing behavior and mechanism toward NO2 by using equivalent circuit modeling achieved by impedance spectroscopic measurements.